Kinetic evaluation of chitosan-derived catalysts for the aldol reaction in water. Issue 11 (29th August 2019) - De Vylder, Anton; Lauwaert, Jeroen; De Clercq, Jeriffa; Van Der Voort, Pascal; Stevens, Christian V.; Thybaut, Joris W.
Abstract : The reaction rate and stability of chitosan as heterogeneous amine catalyst is quantified in a batch and continuous-flow aldol reaction. Abstract : The site time yield (STY) and stability of the primary amine sites in low molecular weight chitosan have been quantified for the aldol reaction of acetone with 4-nitrobenzaldehyde in a mixture of water and acetone as a solvent. Crude chitosan with varying degrees of deacetylation (DDA), as well as chitosan in hydrogel and aerogel forms, was used. Apart from the main reaction, accumulation of an imine formed from 4-nitrobenzaldehyde occurred in the early stages of the reaction. This imine acted as an inhibitor of the primary amine sites and was formed until an equilibrium was reached, after which the catalytic activity remained constant. Chitosan with a DDA amounting to 70.4% exhibited a STY of 2.18 ± 0.05 × 10 −5 molproduct molamine −1 s −1 . This STY increased with decreasing DDA, as a direct result of an increase in amine p K a . No differences in activity were observed between the crude, hydrogel, and aerogel forms of chitosan with the same DDA. Recycling in a second batch experiment allowed reproducing the same performance as that in the first experiment. Under continuous-flow conditions, the activity of chitosan was found to stabilize as a function of the time on stream, after the imine formation has equilibrated. Even though the catalytic activity of these chitosan catalysts was found to be lower than those of the current state-of-the-art catalysts for the aldol reaction, their stability in an aqueous environment opens new perspectives for future catalyst development.